Agricultural low-cost waste adsorption of methylene blue and modelling linear isotherm method versus nonlinear prediction - Yetgin, Senem; Amlani, Merilyn (Clean technologies and environmental policy, 2025)
This study shows that geographically marked wheat hull, named Siyez , rice hull Sarı Kılçık , and Taşköprü Garlic stalk were used as agricultural waste to potential adsorbent materials for removing methylene blue from aqueous solution. Experimental data were evaluated in both equilibrium batch process and kinetic studies. In addition, the factors that affect the adsorption capacities, such as pH solutions, methylene blue concentration, contact time, and temperatures, were also investigated. Obtained data were subject to two constant adsorption models of Langmuir, Freundlich, Temkin, and Dubinin−Radushkevich. The kinetic models (pseudo-first-order, pseudo-second-order, intra-particle diffusion and film diffusion) and thermodynamic parameters were evaluated. The adsorption isotherms, characterized by an excellent fit with the Langmuir model ( R 2 = 0.99) across all adsorbents, underscore the prevalence of monolayer adsorption of methylene blue, in contrast to the Freundlich equation. Adsorption kinetics of the methylene blue onto the adsorbents followed pseudo-second-order kinetic model. According to high regression coefficient ( R 2 ) and minimal values of nonlinear error functions like RMSE; the maximum monolayer adsorption capacities of wheat hull, rice hull and garlic stalk were found to be 62.50 (mg/g), 54.94 (mg/g), and 370.37 (mg/g), respectively. The results indicated that these proposed adsorbents could be low-cost and effective adsorbents for water purification and have adsorption capacity as much as comparable with the literature. In batch equilibrium studies, the adsorption of methylene blue dye onto the wheat hull, rice hull, and garlic stalk exhibited a significant correlation with temperature, contact time, and initial concentration of methylene blue dye and Adaptive Neuro-Fuzzy Inference System algorithm for forecasting overall the system parameter well fitted with these findings with the accuracy of outputs ( R 2 about 0.99 for each). Consequently, the thermodynamic analysis revealed that the adsorption process takes place in bulk diffusion by liquid phase mass transfer and occurred spontaneously with endothermically except garlic stalk. Adsorption thermodynamic studies show that the adsorption of methylene blue onto the garlic stalk was spontaneous and exothermic. Graphical Abstract